Penggunaan Bungkil Inti Sawit Fermentasi oleh Jamur Pleurotus ostreatus dalam Ransum terhadap Performans Ayam Broiler - Noferdiman, Noferdiman (Fakultas Peternakan Universitas Jambi, 2011)
The experiment was aimed to determine the effect of Palm Kernel Cake fermentation by Pleurotus ostreatus (BISF) in ration on the performance of broiler chicken. The experiment was assigned into Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments were level of BISF into the ration (P0 : 0%, P1 : 10 %, P2 : 20 %, and P3 : 30 %). The observed variables were the feed consumption, body weight gain, feed conversion ration, carcass percentage, and the percentage of abdominal fat. The result of this study showed that added BISF were significantly (P<0.01) feed consumption, body weight gain, feed conversion ration, carcass percentage, and the percentage of abdominal fat. The experiment showed the that fermentation of Palm Kernel Cake (BISF) could be fed to the broiler chicken up to 20 %.